Alih Kode Campur Code dalam Percakapan di Pasar Bang Mego Kecamatan Curup Kabupaten Rejang Lebong - Ifnaldi, Ifnaldi (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2022)
This study aims to answer the questions (1) Does code switching occur in interactions between native Minangkabau speakers when communicating with other people in Curup?; (2) Does code mixing exist in their interactions?; and (3) What are the possible motives for code-switching and code-mixing in their interactions? Although this research is simple, it can be considered as a first step to study code-switching and code-mixing more comprehensively, especially among native Minangkabau speakers in Curup. Through this small study, it can be concluded that native speakers of the Minangkabau language use Indonesian in their interactions with other people. They switch the code to Minangkabau every time the person they are talking to starts using it. The second reason for code switching for them is because they tend to use Minangkabau language if they know that the other person is a speaker of that language. They tend to use Minangkabau language if that language is used by them since the first time they meet.